2016
DOI: 10.1080/1747423x.2016.1172129
|View full text |Cite
|
Sign up to set email alerts
|

Translating land-use science to a museum exhibit

Abstract: For land use science to engage the general public it must successfully translate its concepts and conclusions and make them public outside of traditional scientific venues. Here we explore science-art exhibits, which blend artistic presentations with specific scientific data or themes, as a possible effective way of communicating scientific information and disrupting misconceptions. We describe the process of producing a science-art exhibit on remote sensing and Puerto Rican landscape history from 1937 to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Many studies in this area have chosen to take a look at the combination of scientific research and art as a way to enhance the communication of scientific data to the public. Arce-Nazario (2016) found that an exhibition in Puerto Rico that blended scientific data and artistic presentation was successful in communicating scientific ideas and knowledge, specifically in changing visitors’ misconceptions about Puerto Rico’s history of landscape change. Neal (2015) provided an explanation for such beneficial effects of art, describing art as a frame for social and visual experiences, which have the ability to bridge people and institutions and lay open their emotional and aesthetic connections with the world they live in.…”
Section: Communicating Information In An Engaging Formmentioning
confidence: 99%
“…Many studies in this area have chosen to take a look at the combination of scientific research and art as a way to enhance the communication of scientific data to the public. Arce-Nazario (2016) found that an exhibition in Puerto Rico that blended scientific data and artistic presentation was successful in communicating scientific ideas and knowledge, specifically in changing visitors’ misconceptions about Puerto Rico’s history of landscape change. Neal (2015) provided an explanation for such beneficial effects of art, describing art as a frame for social and visual experiences, which have the ability to bridge people and institutions and lay open their emotional and aesthetic connections with the world they live in.…”
Section: Communicating Information In An Engaging Formmentioning
confidence: 99%
“…Consistent with our predictions, students in both the art and abstract learning treatments had higher comprehension scores than the control group, indicating that students were able to acquire knowledge through both learning treatments. Similarly, other studies have found that integrating art into science education can be effective for enhancing science knowledge in undergraduate students ( 20 , 35 , 36 ). However, some studies have found that art can hinder education, either by oversimplifying complex issues ( 37 ) or by communicating in an overly subtle or abstract way ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 65%
“…To examine the impact of art on public interest and student comprehension of science, we chose to develop an art exhibit, as science art exhibits have been shown to engage wider audiences in science and clarify misunderstandings about certain science topics ( 20 , 21 ), as well as supporting the development of critical thinking skills in the classroom ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…Art is a way to connect our science to the broader public. Science‐art collaborations can be effective for transmitting concepts and reshaping misconceptions (Arce‐Navario 2016). Art can act as a framework for visual and social experiences, which can create empathy toward the natural environment, generating appreciation and concern simultaneously (Marks et al 2016).…”
Section: Figmentioning
confidence: 99%